2021
DOI: 10.1111/ajd.13575
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topical versus intradermal injection of Tranexamic Acid In Egyptian melasma Patients: A randomised clinical trial

Abstract: Background: Melasma is one of the common pigmentary problems affecting females in our community, owing to the frequent use of hormonal contraceptives as well as our sunny climate. A lot of treatment options are available but none of them is completely satisfactory. Many patients prefer the use of topical preparations and minimally invasive methods. Tranexamic acid (TA) is a potential treatment option for hyperpigmentation with different delivery routes. Aim:We designed the study in order to evaluate the effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The MASI scores decreased by 39.1% for the 4 mg/ml, 62.7% for the 10 mg/ml group with no significant difference between them ( p = 0.070). The topical MASI group decreased by 4.2%, which was significantly different than both intralesional groups 42 …”
Section: Introductionmentioning
confidence: 62%
“…The MASI scores decreased by 39.1% for the 4 mg/ml, 62.7% for the 10 mg/ml group with no significant difference between them ( p = 0.070). The topical MASI group decreased by 4.2%, which was significantly different than both intralesional groups 42 …”
Section: Introductionmentioning
confidence: 62%
“…On the contrary, a subsequent RCT by Badran et al reported significantly higher reduction in MASI score with different concentrations of TXA mesotherapy (4 mg/cc and 10 mg/cc) compared to topical TXA 10% cream (39.1%, 62.7%, and 4.2%, respectively). Irritation was reported in topical therapy group, and pain was reported in mesotherapy groups 19 …”
Section: Discussionmentioning
confidence: 98%
“…Injections were performed at 1 mm depth and 1 cm distance by 28–30‐gauge insulin syringe. Follow‐up periods were between 1 and 12 months 7–33 . Based on published articles, significant reductions in melasma area and severity index (MASI) scores were reported with TXA mesotherapy, from 33.3% to 81.2%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations